2016
DOI: 10.1007/s12528-016-9109-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of e-textbook instructor annotations on learner performance

Abstract: With additional features and increasing cost advantages, e-textbooks are becoming a viable alternative to paper textbooks. One important feature offered by enhanced e-textbooks (etextbooks with interactive functionality) is the ability for instructors to annotate passages with additional insights. This paper describes a pilot study that examines the effects of instructor e-textbook annotations on student learning as measured by multiple-choice and open-ended test items. Fifty-two college students in a business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…In a more recent study, however, Dennis et al (2016) found that students learning with e-text outperformed their paper text peers on some types of quizzes. At the same time, a comparative study of fully online students and fully face-to-face students found that e-text usage correlated with increased academic performance in the online group but made no difference for the face-to-face students (Biranvand and Khasseh 2014).…”
Section: The Advantages Of E-textsmentioning
confidence: 84%
See 2 more Smart Citations
“…In a more recent study, however, Dennis et al (2016) found that students learning with e-text outperformed their paper text peers on some types of quizzes. At the same time, a comparative study of fully online students and fully face-to-face students found that e-text usage correlated with increased academic performance in the online group but made no difference for the face-to-face students (Biranvand and Khasseh 2014).…”
Section: The Advantages Of E-textsmentioning
confidence: 84%
“…Receiving instructor feedback via e-text annotation functions appeared to give students a slight advantage when performing on open-end quizzes, while no difference in test results were registered between e-text and paper-based learning cohorts when measuring their performance via multiple-choice quizzes (Dennis et al 2016). The authors concluded that such an e-text affordance as feedback provision via the annotation function could in fact lead to higher-level learning.…”
Section: The Advantages Of E-textsmentioning
confidence: 94%
See 1 more Smart Citation
“…E-textbooks are different from e-books, because they are used for studying a subject that is usually part of a course. There is debate in the literature about whether it is advantageous to adopt e-textbooks and if they positively influence students' learning performance (Baker, Al-Gahtani, & Hubona, 2010;Dennis, Abaci, Morrone, Plaskoff, & McNamara, 2016;Fischer, Hilton, Robinson, & Wiley, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…83-84) We are not alone. Alan Dennis and his team at Indiana University have conducted a number of studies of e-reader use at their institution (Dennis, 2011;Dennis, Morrone, Plaskoff & McNamara, 2015;Dennis, Abaci, Morrone, Plaskoff & McNamara, 2016). They begin with assumptions that we share about the importance of critical reading skills for learning:…”
mentioning
confidence: 99%